Pengembangan Minat Anak SD Melalui Pengenalan Profesi Dosen Di SDN 1 Jahitan - Zebua, Dermawan; Soleman, Agnesia Yolanda; Gulo, Linus Syah Putra (CV. SINAR HOWUHOWU, 2024)
Kelas Inspirasi is a movement aimed at inspiring students by inviting professionals to share stories about their professions. Kelas Inspirasi Seruyan, in collaboration with Pendidik Jahitan and professionals, aims to increase students' interest and knowledge about the profession of lecturers at SDN 1 Jahitan, Desa Jahitan. This program uses an initial survey method to identify students' levels of knowledge and interest, followed by the preparation of introduction materials about the lecturer profession tailored to the understanding level of elementary school students. The activities are conducted using various interactive methods such as presentations, interactive discussions, and simulations. The results of the program showed a significant increase in students' interest and understanding of the lecturer profession, with interest rising from 20% to 85% after the program. Interactive methods proved to be more effective than traditional lectures in increasing students' interest and understanding. These findings indicate that introducing professions through direct interaction with practitioners can be effectively implemented in various elementary schools, motivating students to aim higher and providing them with a strong reason to stay in school. Therefore, the author feels successful in carrying out the Community Service Program at SDN 1 Jahitan.